(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The category of "green" investment is defined as the funds of international climate funds (primarily the Green Climate Fund, funds of EU funds and other international organizations), funds of the budget of states, communities, enterprises and citizens, which are used to preserve and improve the environment and climate on the planet. Climate innovations, primarily aimed at stimulating the production of renewable energy, have become an important object of "green" investments in recent years. The necessity of using "green" investments both in the period of martial law and in the period of reconstruction of the economy of Ukraine is substantiated. The structure of "green" investments, their contribution to the creation of "green" workplaces has been clarified, and the mechanism of their functioning at different levels of management has been developed; the possible risks of international "green" investment in Ukraine during the reconstruction period are determined; an insurance system for "green" investments was developed; existing problems in the use of "green" investments in Ukraine to ensure the conditions of sustainable development were identified. Since Ukraine has the status of a candidate for joining the EU, it is important to develop an effective "green investment" mechanism that would correspond to the requirements of the European community. Ukrainian producers-exporters of goods to the EU must be ready for the introduction of a tax on greenhouse gas emissions. For Ukraine, a new source of funding for the development of the "green" economy and relevant investments could be the creation of the Green Investment Fund of Ukraine, which can be formed due to the gradual reduction of VAT refunds to Ukrainian exporters, as well as from part of the funds received from the privatization of state property. The distribution of the funds of the Green Investment Fund of Ukraine could take place on a competitive basis, taking into account the priority of environmental problems.